Slovene critical responses to the works of Pearl S. Buck - Alenka Blake (Acta Neophilologica, 2003)
At the beginning of her writing career, in the 1930's and 40's, Pearl S. Buck achieved great success that reached its pinnacle with the Nobel Prize for Literature in 1938. Her works were ad mired among readers around the world, including Slovene readers. It seems that the Slovenes did not lag behind the world's literary trends of the time. The first translation of The Good Earth, probably the writer's most prominent novel, in 1934- only three years after the original was writ ten. The subject matter that the writer introduced in her works, China in interaction with the West, attracted many readers and soon resulted in a number of works being translated into Slovene. Con sequently the amount of critical material in Slovene newspapers and magazines also began to rise. This article provides an overview of and assesses the Slovene critical material on Pearl S. Buck, while evaluating the literary quality of that material.